Analysis of Asset Administration on the Performance of Regional Financial Statements in East Nusa Tenggara Province - Yosaphat Maryo Diaz; Julia Safitri; Prisilia Damayanti (Mandalika Institute, 2026)
Currently, public demands for good governance are increasing. Therefore, the performance of Regional Work Units (OPD) must be improved to produce quality financial reports. This study aims to analyze the influence of human resources, leadership commitment, and asset user behavior on financial report presentation performance, with transparency and accountability as mediating variables, in OPDs within the East Nusa Tenggara Provincial Government. The novelty of this study lies in the integration of Stewardship Theory and the Resource-Based View (RBV) to examine asset administration factors and the mediating role of transparency and accountability in explaining financial report presentation performance in the public sector. This research is based on the integration of Stewardship Theory and the Resource-Based View (RBV) to explain the factors influencing local government financial report presentation performance. Based on the analysis using the SEM-PLS approach, it was found that human resources and leadership commitment did not significantly influence financial report presentation performance, directly or indirectly. Conversely, asset user behavior was shown to have a positive and significant influence on financial report presentation performance, both directly and through transparency and accountability. These findings highlight the importance of strengthening responsible asset management behavior and enhancing transparency and accountability mechanisms to improve the quality of regional government financial reporting and support good governance practices.